A method for preparing a ZIF-8 / polyvinyl alcohol-based full heat exchange membrane

By adopting the preparation method of ZIF-8/polyvinyl alcohol-based full heat exchange membrane, the existing full heat exchanger membrane materials are easily moldy, bacterial breeding and insufficient gas barrier performance, and efficient gas barrier and water are achieved The vapor passes through, enhancing antibacterial properties and simplifying the preparation process.

CN118718770BActive Publication Date: 2025-02-25SHAOXING JIANMIAO NEW MATERIAL TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411191562.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-02-25
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

The paper film used in existing full heat exchangers lacks gas barrier properties, is prone to mold and breeds bacteria, has a short service life and is complex in preparation process, which limits the popularity of full heat exchangers.

Method used

Using the preparation method of ZIF-8/polyvinyl alcohol-based full heat exchange membrane, by dissolving polyvinyl alcohol in hot water in 50°C and stirring at 80°C, a dense membrane structure was formed, combining ZIF-8 nanoparticles. The cast film liquid is mixed and coated on the microporous base film, and naturally dried to form a full heat exchange film.

Benefits of technology

The gas barrier properties and water vapor transmittance of the full heat exchange membrane are improved, antibacterial properties are enhanced, service life is extended, and the preparation process is simplified, which reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118718770B_ABST
    Figure CN118718770B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of total heat exchange, and specifically to a method for preparing a ZIF‑8 / polyvinyl alcohol-based total heat exchange membrane. The present invention is aimed at the problems that the total heat exchange membrane is easy to mold, easy to breed bacteria, not air-blocking and has low total heat exchange efficiency, and provides a method for preparing a ZIF‑8 / polyvinyl alcohol-based total heat exchange membrane. First, polyvinyl alcohol particles are placed in 50°C hot water and stirred at a constant temperature for 30 minutes, then the temperature is raised to 80°C and stirred for 40 minutes, then ZIF‑8 and hydrophilic components are dissolved in deionized water and stirred at 60°C for 30 minutes, and finally the above two solutions are mixed evenly in proportion to form a casting liquid, and the casting liquid is centrifuged and applied to one side of the substrate, and is naturally dried to make a total heat exchange membrane. The total heat exchange membrane prepared by the present invention has high total heat exchange efficiency and antibacterial properties, and has good application prospects in the field of total heat exchange.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of total heat exchange, and in particular relates to a method for preparing a ZIF-8 / polyvinyl alcohol-based total heat exchange membrane. Background Art

[0002] As an air conditioning auxiliary device, the total heat exchanger utilizes the fresh air system that recycles the heat energy of the exhaust air and reuses it for the supply air. It uses efficient heat exchange elements to exchange heat between the exhaust air and the supply air. The total heat exchanger uses the total heat exchange membrane to allow outdoor fresh air and indoor dirty air to exchange heat and recover moisture in a closed heat exchange core, while maintaining a comfortable room temperature and continuously bringing fresh and clean air. At present, most of the total heat exchanger products on the market use paper membrane as the total heat exchange membrane, but the paper membrane has almost no gas barrier properties and cannot block waste gases such as CO2 in the exhaust air, which is easy to cause cross contamination. In addition, the paper membrane is prone to mold, has a short service life, low mechanical strength, and cannot be washed, which restricts the popularity of the total heat exchanger.

[0003] Membrane dehumidification has aroused a research boom due to its advantages of low energy consumption and washability. The main research is to prepare various heat exchange membranes with excellent moisture permeability, high gas barrier, mildew resistance and flame retardancy through the compounding of different membrane materials and additives, so as to replace paper membranes to more effectively reduce air conditioning energy consumption and improve indoor air quality. For example, by introducing hydrophilic functional groups to effectively improve water transfer, such as polyamide, polyvinyl alcohol, chitosan and cellulose, they have been used to construct water molecule transfer channels. Ni Jia et al. studied the compounding of polyvinyl alcohol with water-soluble chitosan and acid-soluble chitosan, and prepared heat exchange membranes with water vapor permeability. The results showed that the water resistance of the heat exchange membrane prepared by acid-soluble chitosan was much better than that of the heat exchange membrane prepared by water-soluble chitosan. However, the article used glacial acetic acid as an organic solvent to dissolve acid-soluble chitosan. Glacial acetic acid is very volatile and has certain toxicity. It can irritate the mucous membranes of the respiratory tract, skin, eyes and other parts, causing harm to the human body. Chinese patent CN201310041806.0 discloses an antibacterial and mildew-proof full heat exchange membrane, which is obtained by coating a functional layer containing a polymer, a porous material antibacterial agent and a hygroscopic agent on a substrate such as cellulose paper to obtain an antibacterial and mildew-proof full heat exchange membrane with high enthalpy exchange efficiency. However, the polymer used in this patent is a water-soluble material, which will swell or even dissolve after adding a hygroscopic agent, resulting in the antibacterial effect being difficult to last, and may even result in the failure of the full heat exchange membrane to leak. To this end, Chinese patent CN 202010657696.0 discloses a method for preparing water-resistant full heat exchange paper, which adds a polymer film-forming substance and an antibacterial and mildew-proof material to a solvent to obtain a coating solution, and uses a screen roller to apply the coating solution to a low-permeability paper, and dries to obtain a high-permeability, dense full heat exchange membrane, but this invention requires the use of an organic solvent to prepare the coating solution, and the antibacterial and mildew-proof material used has the disadvantage of low toxicity, which limits its application.

[0004] Chinese patent CN 202010674648.2 "A method for preparing an antiviral full heat exchange fresh air membrane" discloses a method for preparing an antiviral full heat exchange fresh air membrane, first preparing a quaternary ammonium salt polymer, then dissolving the quaternary ammonium salt polymer and a high moisture permeability polymer in a solvent to obtain a coating solution, and finally coating the coating solution on a porous substrate, and drying to obtain an antiviral full heat exchange fresh air membrane. However, the quaternary ammonium salt polymer in this patent is easily hygroscopic and hydrolyzed, making it not resistant to water washing, and after film formation, the film is prone to adhesion and dirt absorption due to its positive charge. To this end, Chinese patent CN202310730535.3 discloses a method for preparing a washable full heat exchange fresh air membrane, in which a polymer generated by copolymerization is dissolved in a solvent to obtain a coating liquid, and a washable full heat exchange fresh air membrane is obtained by coating the coating liquid on a porous base membrane and drying it. However, this invention requires nitrogen protection and needs to be carried out at 80-90°C for 48-72 hours, with strict experimental conditions and a long preparation cycle.

[0005] Metal organic frameworks (MOFs), especially zinc imidazole framework (ZIF) nanoparticles, have been widely used to prepare mixed matrix polyamide separation membranes that can achieve efficient water purification. ZIF nanoparticles include ZIF-7, ZIF-8 and ZIF-67. ZIF nanoparticles are hydrophilic by increasing the surface roughness of the membrane, and the ZIF nanoparticles have selective hydrophilic channels inside, which can provide more channels for the transmission of water molecules. Due to the excellent hydrophilic and antibacterial effects of ZIF nanoparticles, they have been introduced and used in the field of total heat exchange membranes. For example, the paper "ZIF / PA thin film nano-composite (TFN) total heat exchange membranes (THEMs): Preparation, performance and integrated online testing" published by Xue Lixin's team introduced ZIF nanoparticles in the interfacial polymerization step to prepare nanocomposite polyamide total heat exchange membranes. Chinese patent CN 202310221705.5 "Total heat exchange membrane with rough surface structure containing special-shaped ZIF-8 microcrystalline leaves and its preparation method" discloses a total heat exchange membrane with ultra-rough surface structure based on special-shaped ZIF-8 microcrystalline leaves and its preparation method. The invention first dissolves polyethyleneimine and zinc compounds in deionized water to obtain a polymer solution, then adds the polymer solution to a plate frame with a support material and allows it to stand, then dissolves the imidazole ligand in deionized water and adds it to the plate frame for reaction, and finally pours out the supernatant in the frame, dries the finished film into a film, and obtains a total heat exchange membrane with a rough surface structure based on special-shaped ZIF-8 microcrystalline leaves. However, the growth of interfacial polymerization-grown ZIF-8 is affected by the temperature and reaction time of the reaction solution, which affects the macroscopic morphology of the ZIF-8 particles synthesized on the membrane surface, thereby affecting the performance of the membrane, the operation is complicated, and the production application is limited. Therefore, a new method for introducing ZIF nanomaterials is urgently needed. Summary of the invention

[0006] In summary, the present invention is aimed at the problems of easy mold, easy breeding of bacteria, no air blocking and low total heat efficiency of the total heat exchange membrane, and provides a method for preparing a ZIF-8 / polyvinyl alcohol-based total heat exchange membrane. The present invention first puts polyvinyl alcohol into 50°C hot water, and stirs it at a constant temperature in a water bath for 30 minutes, so that the polyvinyl alcohol swells and dissolves first, and then heats it to 80°C and stirs it at a constant temperature for 40 minutes to completely dissolve the polyvinyl alcohol and then stands for use. Compared with direct heating, this invention shortens the stirring time of polyvinyl alcohol at high temperature, reduces the decomposition of polyvinyl alcohol, increases the viscosity and crystallinity of the polyvinyl alcohol solution, and the prepared polyvinyl alcohol film has a dense structure, improves the gas barrier property of the film, reduces the swelling of the film, and thus increases the service life. The difference between the present invention and the above-mentioned interfacial polymerization method that introduces ZIF nanomaterials is that the present invention blends a certain mass ratio of ZIF-8, polyvinyl alcohol and other hydrophilic components to prepare a casting solution, but because ZIF-8 is insoluble in water, the blend is prone to precipitation and uneven dispersion when it is left to stand. Therefore, the present invention applies the casting liquid to the microporous base membrane after centrifugation at 4000rpm for 5min, and forms a full heat exchange membrane after natural drying. The prepared full heat exchange membrane has high water vapor permeability, high gas barrier properties and antibacterial properties. In the embodiment of the present invention, the composite membrane with ZIF-8 added is compared with the composite membrane with quaternary ammonium salt polymer added, and a preparation method of ZIF-8 / polyvinyl alcohol-based full heat exchange membrane is provided. The specific steps are as follows:

[0007] Step 1: First, dissolve polyvinyl alcohol in 50°C hot water, and stir it in a water bath at a constant temperature of 600-1200r / min for 30 minutes. Then heat it to 80°C and stir it at a constant temperature of 400-600r / min for 40 minutes to prepare a polyvinyl alcohol solution with a mass fraction of 4%-6%, and let it stand for use.

[0008] Step 2: Dissolve ZIF-8 and hydrophilic components in a certain mass ratio in deionized water, stir at a constant temperature of 400-600 r / min at 60° C. for 30 min, and then stand for use.

[0009] Step 3: Prepare a casting solution by mixing the solutions in step 1 and step 2 at a mass ratio of 4 to 1:1.

[0010] Step 4: Centrifuge the casting solution in step 3 at 4000 rpm for 5 min and let it stand for later use.

[0011] Step 5: Apply the casting solution in step 4 to one side of the substrate with a coating thickness of 2 to 5 µm. After natural air drying, it can be used as a full heat exchange membrane.

[0012] The present invention has the following outstanding advantages:

[0013] 1) High gas barrier properties and short preparation cycle. In the present invention, polyvinyl alcohol is first dissolved in 50°C hot water and stirred at a constant temperature for 30 minutes, and then heated to 80°C and stirred at a constant temperature for 40 minutes. Compared with direct heating, this method shortens the stirring time of polyvinyl alcohol at high temperature, increases the viscosity and crystallinity of the polyvinyl alcohol solution, and the prepared polyvinyl alcohol film has a dense structure, high gas barrier properties, reduces the swelling of the film, and thus increases the service life.

[0014] 2) High water vapor permeability, antibacterial properties, and simple and easy process. Unlike the in-situ interfacial polymerization growth of ZIF-8, the present invention blends ZIF-8, polyvinyl alcohol and other hydrophilic components to prepare a casting solution, which is easy to operate. On the one hand, ZIF-8 nanoparticles can increase the surface roughness of the polyethylene film, and the selective hydrophilic channels inside the ZIF-8 nanoparticles can provide more channels for the transmission of water molecules, thereby improving the water vapor permeability. On the other hand, ZIF-8 materials can oxidize pathogenic bacteria in the air to death under the catalytic action of sunlight. Compared with the full heat exchange membrane prepared using quaternary ammonium salt polymers in Chinese patent CN 202010674648.2 "A method for preparing an antiviral full heat exchange fresh air membrane", it has a higher water vapor permeability and antibacterial properties, which solves the problems of traditional paper membranes that are prone to bacterial growth and short life.

[0015] 3) Low cost. In the present invention, 6 ml of casting solution can prepare one square meter of full heat exchange membrane, and the ZIF-8 content is low, which is lower in cost than in-situ interfacial polymerization growth of ZIF-8. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1a Illustration of the antibacterial test of Example 1 of the present invention.

[0017] Figure 1b Illustration of the antibacterial test of Example 2 of the present invention.

[0018] Figure 1c Illustration of the antibacterial test of Example 3 of the present invention.

[0019] Figure 2a This is an illustration of the antibacterial activity test of Comparative Example 1.

[0020] Figure 2b This is an illustration of the antibacterial activity test of Comparative Example 2.

[0021] Figure 3a This is a scanning electron microscope image of the surface of the substrate of the present invention.

[0022] Figure 3b This is a scanning electron microscope image of the coating surface of the full heat exchange membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below in conjunction with specific embodiments and comparative examples. It should be understood that the specific examples and comparative examples are only used to explain and introduce the invention and cannot limit the scope of application of the present invention. Any modifications and changes made to the present invention fall within the protection scope of the present invention without departing from the purpose and scope of the present invention.

[0024] Embodiment 1:

[0025] Step 1: First, dissolve 4 g of polyvinyl alcohol in 100 ml of 50°C hot water, and stir at a constant temperature of 600 r / min in a water bath for 30 min, then heat to 80°C and stir at a constant temperature of 400 r / min for 40 min, and let it stand for use.

[0026] Step 2: Dissolve 0.01 g ZIF-8, 3 g lithium bromide and 3 g sodium alginate in 100 ml deionized water and stir at 60° C. and 400 r / min for 30 min, then stand for use.

[0027] Step 3: Take 80g of the solution in step 1 and 20g of the solution in step 2, mix them together to prepare a casting solution, stir them evenly and set aside.

[0028] Step 4: Centrifuge the casting solution in step 3 at 4000 rpm for 5 min and let it stand for later use.

[0029] Step 5: Apply the casting solution in step 4 to one side of a substrate with an air permeability of 180sec / 100cc, with a coating thickness of 2µm, and use it as a full heat exchange membrane after natural air drying.

[0030] Embodiment 2:

[0031] Step 1: First, dissolve 5g of polyvinyl alcohol in 100ml of 50℃ hot water, stir it in a water bath at a constant temperature of 1000r / min for 30min, then heat it to 80℃ and stir it at a constant temperature of 500r / min for 40min, and let it stand for use.

[0032] Step 2: Dissolve 0.03 g ZIF-8, 2 g diatomaceous earth and 1 g starch in 100 ml deionized water, stir at 60° C. and 500 r / min for 30 min, and let stand for use.

[0033] Step 3: Take 40 g of the solution in step 1 and 40 g of the solution in step 2, mix them together to prepare a casting solution, stir them evenly and set aside.

[0034] Step 4: Centrifuge the casting solution in step 3 at 4000 rpm for 5 min and let it stand for later use.

[0035] Step 5: Apply the casting solution in step 4 to one side of a substrate with an air permeability of 200sec / 100cc, with a coating thickness of 3µm, and use it as a full heat exchange membrane after natural air drying.

[0036] Embodiment 3:

[0037] Step 1: First, dissolve 6 g of polyvinyl alcohol in 100 ml of 50°C hot water, and stir at a constant temperature of 1200 r / min in a water bath for 30 min, then heat to 80°C and stir at a constant temperature of 600 r / min for 40 min, and let it stand for use.

[0038] Step 2: Dissolve 0.05 g ZIF-8, 3 g lithium bromide and 1 g polyglutamic acid in 100 ml deionized water, stir at 60° C. and 600 r / min for 30 min, and let stand for use.

[0039] Step 3: Take 60g of the solution in step 1 and 20g of the solution in step 2, mix them together to prepare a casting solution, stir them evenly and set aside.

[0040] Step 4: Centrifuge the casting solution in step 3 at 4000 rpm for 5 min and let it stand for later use.

[0041] Step 5: Apply the casting solution in step 4 to one side of a substrate with an air permeability of 240sec / 100cc, with a coating thickness of 3µm, and use it as a full heat exchange membrane after natural air drying.

[0042] Comparative Example 1:

[0043] Step 1: Dissolve 4 g of polyvinyl alcohol, 3 g of lithium bromide and 1 g of chitosan quaternary ammonium salt in 200 ml of deionized water, and stir at a constant temperature of 80° C. for 2 h in a water bath to prepare a casting solution and let it stand for use.

[0044] Step 2: Apply the casting solution in step 1 to one side of a substrate with an air permeability of 180sec / 100cc, with a coating thickness of 2µm, and use it as a full heat exchange membrane after natural air drying.

[0045] Comparative Example 2:

[0046] Step 1: Dissolve 6 g of polyvinyl alcohol, 3 g of diatomaceous earth and 3 g of chitosan quaternary ammonium salt in 200 ml of deionized water, and stir at a constant temperature of 60° C. for 2 h in a water bath to prepare a casting solution and let it stand for use.

[0047] Step 2: Apply the casting solution in step 1 to one side of a substrate with an air permeability of 240sec / 100cc, with a coating thickness of 5µm, and use it as a full heat exchange membrane after natural air drying.

[0048] Test method:

[0049] For the embodiments and comparative examples of the present invention, the water vapor permeability of the total heat exchange membrane was evaluated by the method of "GB / T 1037-2021 Plastic film and sheet water vapor permeability determination cup weight gain and weight loss method".

[0050] The gas barrier properties of the full heat exchange membrane were evaluated using the "GB / T 1038.1-2022 Test method for gas permeability of plastic films and sheets - Differential pressure method" method.

[0051] The antibacterial properties of total heat exchange membrane were evaluated using the "GB / T 20944 Oscillation method for evaluation of antibacterial properties of textiles" method.

[0052] The test results of water vapor permeability and gas permeability of the total heat exchange membranes prepared in the examples of the present invention and the comparative examples are shown in Table 1.

[0053] Table 1

[0054] Example <![CDATA[Water vapor transmission rate g / (m 2 ·24 h)]]> <![CDATA[Gas permeability (l / m 2 / h / bar)]]> Example 1 4809.5 7250 Example 2 5845.6 8763 Example 3 6869.6 8974 Comparative Example 1 3948.07 59876 Comparative Example 2 4259.87 69870

[0055] The antibacterial property test of the total heat exchange membrane prepared by the present invention is shown in the attached figure. Figure 1a , Figure 1b and Figure 1c These are the antibacterial test examples of Example 1, Example 2 and Example 3 of the present invention, Figure 2a and Figure 2b They are the antibacterial test examples of comparative example 1 and comparative example 2, and it can be seen from the comparison that the total heat exchange membrane containing ZIF-8 has better antibacterial properties.

[0056] The scanning electron microscope image of the substrate of the present invention and the scanning electron microscope image of the coating surface of the full heat exchange membrane prepared in Example 1 are shown in the attached drawings. Figure 3a This is a scanning electron microscope image of the surface of the substrate of the present invention, showing a porous morphology. Figure 3b This is a scanning electron microscope image of the coating surface of the full heat exchange membrane of Example 1 of the present invention, which shows a non-porous and dense morphology. By comparing the two images, it can be seen that Example 1 of the present invention successfully prepared a dense coating on the surface of the base membrane, thereby improving the gas barrier properties.

[0057] Conclusion: Compared with the comparative example, the total heat exchange membrane with ZIF-8 added has obvious antibacterial properties than the total heat exchange membrane with quaternary ammonium salt polymer added, and the gas barrier property of the total heat exchange membrane with ZIF-8 added is significantly improved. The ZIF-8 / polyvinyl alcohol-based total heat exchange membrane of the present invention not only has antibacterial properties, but also has efficient total heat exchange performance.

Claims

1. A method for preparing a ZIF-8 / polyvinyl alcohol-based total heat exchange membrane, characterized in that: The preparation method comprises the following steps: S1. First, dissolve polyvinyl alcohol with a degree of alcoholysis of 87% to 89%; S2, dissolving ZIF-8 and the hydrophilic component in a mass ratio of (1-5):(200-400) in deionized water, stirring at a constant temperature of 400-600 r / min at 60° C. for 30 min, and then standing for use; S3, preparing a casting solution by mixing the solutions in S1 and S2 at a mass ratio of (4-1):1; S4, centrifuge the casting solution in S3 at 4000 rpm for 5 min and then let it stand for later use; S5, applying the casting solution in S4 to one side of the air-permeable substrate with a coating thickness of 2 to 5 μm, and using it as a full heat exchange membrane after natural air drying; The polyvinyl alcohol dissolving step in S1 is as follows: firstly, the polyvinyl alcohol is placed in hot water at 50°C, and stirred at a constant temperature of 600-1200 r / min in a water bath for 30 minutes, then the temperature is raised to 80°C, and stirred at a constant temperature of 400-600 r / min for 40 minutes, and then allowed to stand for use; The mass fraction of the polyvinyl alcohol solution prepared in S1 is 4% to 6%; The hydrophilic components in S2 include a hygroscopic agent and a polar polymer.

2. The preparation method according to claim 1, characterized in that: The desiccant is one or more of lithium bromide, bleaching earth, calcium sulfate and diatomaceous earth; the polar polymer includes one or more of sodium alginate, chitosan quaternary ammonium salt, starch, protein and polyglutamic acid.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the hygroscopic agent to the polar polymer is (1-3):

1.

4. The preparation method according to claim 1, characterized in that: The air permeability of the substrate in S5 is 180 to 240 sec / 100 cc.

Citation Information

Patent Citations

  • Total heat exchange membrane and total heat exchanger with antibacterial and anti-mildew functions

    CN103877870B

  • Preparation method of antiviral total heat exchange fresh air film

    CN111825881A

  • Preparation method of water-resistant total heat exchange paper

    CN111849001A

  • Total heat exchange membrane containing special-shaped ZIF-8 microcrystalline leaves and having rough surface structure and preparation method of total heat exchange membrane

    CN116212658A

  • Preparation method of washable total heat exchange fresh air membrane

    CN116672906A